Synthesis and Anticancer Activity of Novel Dual Inhibitors of Human Protein Kinases CK2 and PIM-1 - Patrycja Wińska; Monika Wielechowska; Mirosława Koronkiewicz; Paweł Borowiecki (MDPI AG, 2023)
CK2 and PIM-1 are serine/threonine kinases involved in the regulation of many essential processes, such as proliferation, differentiation, and apoptosis. Inhibition of CK2 and PIM-1 kinase activity has been shown to significantly reduce the viability of cancer cells by inducing apoptosis. A series of novel amino alcohol derivatives of parental DMAT were designed and synthesized as potent dual CK2/PIM-1 inhibitors. Concomitantly with the inhibition studies toward recombinant CK2 and PIM-1, the influence of the obtained compounds on the viability of three human carcinoma cell lines, i.e., acute lymphoblastic leukemia (CCRF-CEM), human chronic myelogenous leukemia (K-562), and breast cancer (MCF-7), as well as non-cancerous cells (Vero), was evaluated using an MTT assay. Induction of apoptosis and cell cycle progression after treatment with the most active compound and a lead compound were studied by flow-cytometry-based assay. Additionally, autophagy induction in K-562 cells and intracellular inhibition of CK2 and PIM-1 in all the tested cell lines were evaluated by qualitative/quantitative fluorescence-based assay and Western blot method, respectively. Among the newly developed inhibitors, 1,1,1-trifluoro-3-[(4,5,6,7-tetrabromo-1H-benzimidazol-2-yl)amino]propan-2-ol demonstrates the highest selectivity and the most prominent proapoptotic properties towards the studied cancer cells, especially towards acute lymphoblastic leukemia, in addition to inducing autophagy in K-562 cells.